2014
DOI: 10.7717/peerj.612
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and anti-tubercular activity of 3-substituted benzo[b]thiophene-1,1-dioxides

Abstract: We demonstrated that the 3-substituted benzothiophene-1,1-dioxide class of compounds are effective inhibitors of Mycobacterium tuberculosis growth under aerobic conditions. We examined substitution at the C-3 position of the benzothiophene-1,1-dioxide series systematically to delineate structure–activity relationships influencing potency and cytotoxicity. Compounds were tested for inhibitory activity against virulent M. tuberculosis and eukaryotic cells. The tetrazole substituent was most potent, with a minimu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…tuberculosis . We were able to derive compounds that had good anti-tubercular activity (with MICs of 3–8 μM) but were unable to identify potent compounds analogs that were not cytotoxic to eukaryotic cells [44].…”
Section: Discussionmentioning
confidence: 99%
“…tuberculosis . We were able to derive compounds that had good anti-tubercular activity (with MICs of 3–8 μM) but were unable to identify potent compounds analogs that were not cytotoxic to eukaryotic cells [44].…”
Section: Discussionmentioning
confidence: 99%
“…Using this as a starting point we explored the BTD series and evaluated their activity against M. tuberculosis . We were able to derive compounds that had good anti-tubercular activity (with MICs of 3–8 μM) but were unable to identify potent compounds analogs that were not cytotoxic to eukaryotic cells (44).…”
Section: Discussionmentioning
confidence: 99%
“…Chandrasekera et al tested the potential of newly synthesized 3-substituted benzothiophene-1,1-dioxide derivatives as inhibitors of virulent Mycobacterium tuberculosis. 23 The results revealed that the substitution at the C-3 position of the benzothiophene-1,1dioxide series influenced the anti-tubercular activity. Oxadiazoles 24(a-d) ( Figure 21) showed good anti-tubercular were found equipotent to standard in inhibiting the rat paw edema.…”
Section: Anti-inflammatory Activitymentioning
confidence: 97%